2019
DOI: 10.1097/mot.0000000000000651
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the risk and rewards of utilizing organs from hepatitis C viremic donors

Abstract: Purpose of review: Because of long waitlist times and high waitlist morbidity and mortality, strategies to increase utilization of Hepatitis C viremic deceased donor organs are under investigation in kidney, liver, heart and lung transplantation. Recent findings: Direct-acting antiviral medications for Hepatitis C virus infection have high cure rates and are well tolerated. Small, single-center trials in kidney and heart transplant recipients have demonstrated that with early post-transplant direct-acting anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…Although studies regarding cure rate of HCV infection in the post‐transplant population have demonstrated uniform cure rates of 100%, 6,7 these studies are limited by their small volume. However, these rates are comparable to the 98–100% cure rates observed with DAAs in the general population 8 …”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Although studies regarding cure rate of HCV infection in the post‐transplant population have demonstrated uniform cure rates of 100%, 6,7 these studies are limited by their small volume. However, these rates are comparable to the 98–100% cure rates observed with DAAs in the general population 8 …”
Section: Resultssupporting
confidence: 61%
“…However, these rates are comparable to the 98-100% cure rates observed with DAAs in the general population. 8 A common theme that emerged in most studies was lack of knowledge and concern regarding curability of HCV infection, mentioned by both patients and providers. Although most patients were aware of HCV and its sequelae, Couri et al found that only 60% were aware of whether the disease was curable.…”
Section: Curabilitymentioning
confidence: 99%
“…With the discussion above, it is now possible for patients who are HCV-negative to receive grafts from donors with Hepatitis C virus with proper management before transplantation, and adequate administration of DAA treatment upon transplantation [44]. In applying DAA treatment regimens to improve the viability of HCV-positive organs, there is usually no time to carry out HCV genotyping because of the time pressure associated with organ transplants, and the logistical technicalities [44]. To ease this process, pangenotypic measures are employed, which will cover all HCV-positive organs [44].…”
Section: Transplantation Of Hepatitis-c-positive Organs Under Direct-...mentioning
confidence: 99%
“…In applying DAA treatment regimens to improve the viability of HCV-positive organs, there is usually no time to carry out HCV genotyping because of the time pressure associated with organ transplants, and the logistical technicalities [44]. To ease this process, pangenotypic measures are employed, which will cover all HCV-positive organs [44]. Several regimens have been approved for use over the years.…”
Section: Transplantation Of Hepatitis-c-positive Organs Under Direct-...mentioning
confidence: 99%
See 1 more Smart Citation